GE_GERICHTE P/19470/2025 vom 17. September 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;DROIT D'ÊTRE ENTENDU;DÉNONCIATION CALOMNIEUSE;DIFFAMATION;CALOMNIE | CPP.310; Cst.29; CP.303; CP.173; CP.174